Adjudicated myocarditis and multisystem illness trajectory in healthcare workers post-COVID-19. Issue 1 (23rd February 2023) - Sykes, Robert; Morrow, Andrew J; McConnachie, Alex; Kamdar, Anna; Bagot, C; Bayes, Hannah; Blyth, Kevin G; Briscoe, Michael; Bulluck, Heeraj; Carrick, David; Church, Colin; Corcoran, David; et al.
Abstract : Background: We investigated the associations of healthcare worker status with multisystem illness trajectory in hospitalised post-COVID-19 individuals. Methods and results: One hundred and sixty-eight patients were evaluated 28–60 days after the last episode of hospital care. Thirty-six (21%) were healthcare workers. Compared with non-healthcare workers, healthcare workers were of similar age (51.3 (8.7) years vs 55.0 (12.4) years; p=0.09) more often women (26 (72%) vs 48 (38%); p<0.01) and had lower 10-year cardiovascular risk (%) (8.1 (7.9) vs 15.0 (11.5); p<0.01) and Coronavirus Clinical Characterisation Consortium in-hospital mortality risk (7.3 (10.2) vs 12.7 (9.8); p<0.01). Healthcare worker status associated with less acute inflammation (peak C reactive protein 48 mg/L (IQR: 14–165) vs 112 mg/L (52–181)), milder illness reflected by WHO clinical severity score distribution (p=0.04) and shorter duration of admission (4 days (IQR: 2–6) vs 6 days (3–12)). In adjusted multivariate logistic regression analysis, healthcare worker status associated with a binary classification (probable/very likely vs not present/unlikely) of adjudicated myocarditis (OR: 2.99; 95% CI (1.01 to 8.89) by 28–60 days postdischarge). After a mean (SD, range) duration of follow-up after hospital discharge of 450 (88) days (range 290, 627 days), fewer healthcare workers died or were rehospitalised (1 (3%) vs 22 (17%); p=0.038) and secondary care referrals for post-COVID-19 syndrome were common (42%) and similar to non-healthcare workers (38%; p=0.934). Conclusion: Healthcare worker status was independently associated with the likelihood of adjudicated myocarditis, despite better antecedent health. Two in five healthcare workers had a secondary care referral for post-COVID-19 syndrome. Trial registration number: NCT04403607 .